Coaching, Counseling, Case-Working: Do They Help the Older Unemployed Out of Benefit Receipt and Back into the Labor Market? - Bernhard Boockmann; Tobias Brändle (Institute for the Study of Labor (IZA), 2015)
Job search assistance and intensified counseling have been found to be effective for labor market integration by a large number of studies, but the evidence for older and hard-to-place unemployed individuals more specifically is mixed. In this paper we present key results from the evaluation of "Perspektive 50plus", a large-scale active labor market program directed at the older unemployed in Germany. To identify the treatment effects, we exploit regional variation in program participation. Based on survey evidence, we argue that participation of regions is not endogenous in the vast majority of cases. We use a combination of different evaluation estimators to check the sensitivity of the results to selection, substitution and local labor market effects. We find large positive effects of the program in the range of five to ten percentage points on integration into unsubsidized employment. However, there are also substantial lock-in effects, such that program participants have a higher probability of remaining on public welfare benefit receipt for up to one year after commencing the program.
Keywords: J68; J14; 330; evaluation; active labor market programs; long-term unemployment; older unemployed